Holistic approach to the sustainable commercial property business: analysis of the main existing sustainability certifications - Vieira de Castro, Aliane; Ramírez Pacheco, Gema; Neila González, Fco. Javier (International Journal of Strategic Property Management, 2020)
Sustainability is no longer a new concept. However, applying, measuring and reporting on the sustainability initiative is still a somewhat confused and subjective issue. There is a huge variety of sustainability guidelines and green building schemes of differing natures, meanings and wordings. Despite this, there is no one guideline providing a crossreference between corporate social responsibility and green building performance to help the commercial property market completely incorporate sustainability into their activities. Therefore, this paper intends to link sustainability, real estate environmental, social, and governance (ESG) and sustainable building in order to help companies internalise this concept in all areas of their operations aligning it with their strategic planning. From desk-based research, this proposal examines and compares key aspects of the main schemes in existence, which are currently evolving in the definition, assessment and report of sustainability at the corporate and built environment level. This approach provides key information to help professionals get a better understanding of the specific changes which sustainability brings about in their corporate process, strategies, investment decisions, daily business operations as well as their property management. The insights presented here can support real estate companies to develop comprehensive communication flows and tools for the measurement and disclosure of sustainability data. First published online 24 March 2020